The Influence of Fear of Making Mistakes on Students’ Self-Confidence and Engagement in English Classroom Presentations at MTs Muhammadiyah 1 Samarinda - Shabrina Nur Fadillah; Ade Ismail Ramadhan Hamid; Abdul Halim (Journal of English Language Learning, 2025)
This study examines how the fear of making mistakes influences students’ self-confidence and engagement in English classroom presentations. Speaking anxiety is one of the main psychological obstacles in EFL learning, often driven by fear of negative evaluation, low language proficiency, and past negative experiences. Using a qualitative descriptive method, this research involved eighth-grade students at MTs Muhammadiyah 1 Samarinda who had participated in English speaking tasks. Data were collected through semi-structured interviews to explore their emotional responses, anxiety sources, and coping strategies. The results show that most students experience nervousness and hesitation, primarily due to fear of being judged, making errors, or lacking vocabulary. These factors reduce their confidence and lead to lower participation. However, many students attempt to overcome their fear through calming techniques and self-encouragement. The study also found that peer support and teacher involvement significantly affect student motivation and willingness to speak. These findings highlight the need for supportive classroom environments that encourage risk-taking and normalize mistakes as part of learning. Teachers are advised to provide regular speaking practice, positive reinforcement, and collaborative learning activities to reduce anxiety and enhance student engagement in English presentations.